Urgensi Deradikalisasi dalam Pendidikan Islam di Sekolah - Rohani Shidiq (Edukasia Islamika, 2017)
This article aims to explore the importance of deradicalization in Islamic Education. The research method used in this study is library research method in which the data were collected from various sources. The Research result shows that religious radicalsm is a serious problem whose solution should be found immediately. If it is ignored for a long time, it will bring negative impact and threaten the existence of NKRI. Nowadays, there is a great amount of religious violence that become “an achievement” in the caderization process done by Islamic radicals. Moreover, they have approached to any education levels, starting from secondary school level up to high school level. Therefore, it is necessary to have serious attempts in deradicalizing the Islamic Education taught to the students in order to prevent the growth of radicalization among various religions, languages, racial and ethnic groups.